More than a Decade Later: Library Web Usability Practices at ARL Academic Libraries in 2007 and 2020 - Chen, Yu-Hui; Germain, Carol Anne; Rorissa, Abebe (College & research libraries, 2023)
This study compares library web usability practices in 2007 and 2020 at academic libraries that are institutional members of the Association of Research Libraries. The authors performed chi-square and t-tests to determine whether there were differences in establishing policies/standards/guidelines (PSGs), conducting usability tests, and providing resources between samples of libraries from both years. There was no statistically significant difference between the number of libraries with and without PSGs in both samples. In 2020, the level of perceived importance of usability testing significantly decreased, and the resources needed for web usability initiatives doubled. The authors suggest that academic and research libraries foster a culture of web usability to actualize and optimize usability endeavors.